A Fault-Tolerant Method for Enhancing Reliability of Services Composition Application in WSNs Based on BPEL. (28th March 2013) - Wu, Zhao; Xiong, NaiXue; Han, Wenlin; Huang, Yan N.; Hu, Chun Y.; Gu, Qiong; Hang, Bo
In recent years, some approaches have been presented for the seamless integration of WSNs with the existing, widely deployed SOA technologies such as XML, Web services, and the Business Process Execution Language (BPEL) to build a wireless sensor networks service application. However, there a great challenge on fault tolerant in WSNs. In this paper, we present our framework and approach to enhance the reliability of service composition applications in WSNs through modeling and analyzing a wireless sensor networks service application based on BPEL with exception handler and compensation mechanism. At first, we analyze all possible states during the execution of BPEL instance in WSNs. Then, we present a state framework for modeling execution context in BPEL instance in WSNs. Based on this framework, we analyze state transition and operational semantics in the case of both correct execution and exceptional execution of BPEL instance in WSNs. Furthermore, we propose the state transition models for three types of activities in BPEL instance. In the end, we present a formal approach to model the execution context in BPEL for WSNs. Using this formal model, one can describe and analyze the control flow result from the exception handler and compensation mechanism in BPEL instance for WSNs.